Government Communications in Digital Era: Public Relation and Democracy - Dunan, Amri (Jurnal Pekommas, 2020)
Social media are changing the way government public relations communicate and do their duty. After the enactment of a presidential decree number 9 of 2015, government agencies have been using social media as one of their communication channels. This study aims to analyze how government agencies’ social media accounts  perform two-way communication with the public. It particularly addresses how social media are affecting democracy and the role of public relations professionals in the digital era. A qualitative approach with interviews and observations is carried out for data collection. Analysis of the data using a model of Miles & Huberman (1984) and triangulation to the conclusion. Results indicate that social media can improve the interactivity between a government and the public.